Nosocomial Infections During Extracorporeal Membrane Oxygenation in Pediatric Patients: A Multicenter Retrospective Study - Wang, Chunle; Li, Shuanglei; Wang, Feng; Yang, Jinfu; Yan, Wei; Gao, Xue; Wen, Zhiqiang; Xiong, Yaoyao (Frontiers in Pediatrics, 2022)
Abstract： Objective: Extracorporeal membrane oxygenation (ECMO) is increasingly used in critically ill patients with respiratory and/or cardiac failure. The aim of this study was to investigate the epidemiology, risk of factors and causal organisms of nosocomial infections (NIs) in child patients who underwent ECMO, as well as to evaluate the survival rates of ECMO patients with NIs. Methods: We retrospectively reviewed the medical records of patients who received ECMO support at three hospitals from September 2012 to December 2019. Clinical data of patients who developed NIs were collected and analyzed. Univariate and multivariate analyses were used to investigate predictive factors of NIs during ECMO. Results: A total of 54 first episodes of NIs were identified in the 190 patients on ECMO, including 32 cases of respiratory tract infections, 20 cases of blood stream infections, and 2 cases of surgical site wound infections. The incidence of ECMO-related NIs was 47.6 cases per 1000 ECMO-days. Gram-negative pathogens were the dominant pathogens isolated, accounting for 92.6% of the NIs. In the univariate logistic regression, ECMO mode, ECMO duration, ICU duration and peritoneal dialysis were related with the development of NIs. However, in multivariate analysis, only ECMO duration (OR=2.46, 95%CI: 1.10, 5.51; P=0.029), ICU duration (OR=1.35, 95%CI: 1.05, 1.59; P=0.017) and peritoneal dialysis (OR=2.69, 95%CI: 1.08, 5.73; P=0.031) were the independent predictive factors for NIs during ECMO support. Conclusion: This study identified the significant correlation between ECMO-related NIs and ECMO duration, ICU duration and peritoneal dialysis. Appropriate preventive measures are needed for hospitals to reduce the incidence of ECMO and improve the hospital surveillance in children.